The Influence of Leadership Style and Work Culture on the Work Productivity of Nurses at Mitra Medika Tanjung Mulia Medan General Hospital - Ella Adhisty; Novita Sari; Nurmala Nurmala (Program Pascasarjana UIN Sumatera Utara, 2022)
Every job requires human resources to improve the quality of work, one of the efforts to produce good quality work is to increase work productivity. The importance of productivity for nurses is an evaluation material to make continuous improvements to all components of the hospital, improving the quality of work by the hospital which plays an important role is the approach by leaders and a positive culture in the workplace. The purpose of this study is to determine the effect of leadership style and work culture to produktivity of nurses. This type of research is analytic survey with cross sectional approach. The study population was all nurses at Mitra Medika Tanjung Mulia Hospital Medan as many as 145 people with 106 samples taken by simple random sampling technique. Analyzed using univariate, bivariate analysis using chi-square test with 95% confidence level, using multivariate logistic regression. The results showed that most of the leadership style less, namely 39 respondents (36.8%), work culture enough that 35 respondents (33.0%), labor productivity sufficiently at 42 respondents (39.6%). The results of the analysis of the influence of leadership style statistikmenunjukkan (p = 0.000), and the work culture p = 0.017) on the productivity of nurses in hospital Mitra Medika Tanjung Mulia Medan in 2016. It is recommended to the hospital for further enhancing cooperation and better relations between the leaders with nurse in order to improve the productivity of nurses better.